6+11x=-4x+x

Simple and best practice solution for 6+11x=-4x+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+11x=-4x+x equation:


Simplifying
6 + 11x = -4x + x

Combine like terms: -4x + x = -3x
6 + 11x = -3x

Solving
6 + 11x = -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
6 + 11x + 3x = -3x + 3x

Combine like terms: 11x + 3x = 14x
6 + 14x = -3x + 3x

Combine like terms: -3x + 3x = 0
6 + 14x = 0

Add '-6' to each side of the equation.
6 + -6 + 14x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 14x = 0 + -6
14x = 0 + -6

Combine like terms: 0 + -6 = -6
14x = -6

Divide each side by '14'.
x = -0.4285714286

Simplifying
x = -0.4285714286

See similar equations:

| .05x-.09y=208 | | 7x^2-5=10x | | -20=y-17 | | 2(2x+3)=13x-37 | | 5+x-14=60 | | 0.143x-6=0.43x+4 | | 6(9n-11)-20n=9 | | x^2+4x-12-2=0 | | 6(9n-11)-20n=4 | | 6(9n-11)-20n=n | | -0.7(0.3x-0.8)=4.8 | | 6(9n-11)-20n=2 | | 5+4x-7=4x-2+x | | 1/5x13 | | 4x+9=x+5 | | -(3/8)÷-(5/24) | | 1x+1.75=15 | | 4y+2=-4+10y | | -10+5c=2c+8 | | 65-3x=44 | | y+4=99 | | -2500-4.05x=-3000000 | | 0.08(4h-3)-0.04(5h-2)=0.2 | | -10-6z=-5z | | (5x2-3x-3)(x-1)/x2 | | 2x+9x=31 | | 4b+4=-9 | | -10+3h=2h | | 1b-4=9b | | 7f+10=8f | | 4/7x(-2/9) | | -3v-7=-4 |

Equations solver categories